THE USE OF GOOGLE SITES IN EXTENSIVE LISTENING CLASSROOM: STUDENTS’ VOICES - Muhammad Handi Gunawan; Eisha Sabila Dieni Hanifa; Aninda Putri Gunawan; Didi Suherdi (English Review: Journal of English Education, 2023)
Extensive Listening (EL) is a recent study whose development is sparked by Extensive Reading (ER). However, not many studies have been conducted on the implementation of Extensive Listening in the classroom using digital tools provided on the internet such as Google Sites. This study aims to examine students’ perceptions of the use of Google Sites in extensive listening classes. It was conducted using a qualitative design by involving 18 second-year students at a higher education level. The students’ classroom reflections and the semi-structured style of the interview were included as the research instruments. The results showed that most of the students believed that Google Sites is useful to enhance their creativity and motivate them to be actively involved in extensive listening activities.